THE EFFECT OF LEADERSHIP, WORKING ENVIRONMENT AND COMPENSATION ON COMMITMENT ORGANIZATION, CULTURAL ORGANIZATION, AND PERFORMANCE OF EMPLOYEES (Studies in Dishubinfokom Sukoharjo) - Hartanto, Eko Prih (-)
This study aims to identify and test the effect of: 1) leadership on organizational commitment, 2) work environment on organizational commitment, 3) compensation to organizational commitment, 4) leadership on organizational culture, 5) the working environment of organizational culture, 6) compensation to organizational culture, 7) leadership to employee performance, 8) work environment to employee performance, 9) compensation to employee performance, 10) organizational commitment to employee performance, 11) organizational culture on employee performance Dishubinfokom Sukoharjo. Data collected by the census techniques of civil servants in the Department of Transportation, Information and Communication Sukoharjo number of 57 employees. Analysis of the data used include test research instruments that test the validity and reliability testing; linearity test; and test the hypothesis that the path of regression analysis, t test, F test, coefficient of determination (R2). The regression equation indicates that the Dishubinfokom Sukoharjo: 1) Leadership positive effect, no significant effect on organizational commitment, 2) work environment as well as significant positive effect on organizational commitment, 3) Compensation and no significant positive effect on organizational commitment, 4) Leadership positive influence and no significant effect on organizational culture, 5) a positive working environment as well as significant influence of organizational culture, 6) Compensation not significant and positive influence of organizational culture, 7) Leadership and no significant positive effect on employee performance, 8) work environment as well as the positive effects significantly to the performance of employees, 9) Compensation not significant and positive effect on employee performance, 10) Commitment to the organization as well as no significant negative effect on the performance of employees, 11) Cultural organizations as well as a significant positive influence on employee performance. F test showed that jointly independent variable Organizational Culture, Leadership, Organizational Commitment, Compensation and Working Environment affects employee performance Dishubinfokom Sukoharjo. Results Analysis Derteminasi coefficient (R2) shows the R2 value of 0.976 means the total Dishubinfokom Sukoharjo employee performance can be explained by the Leadership, Organizational Environment, and Compensation with Organizational Commitment and Cultural Organization as an intervening variable of 97.6% and the remaining 2.4% is explained by other variables outside the research model. From the analysis of pathways known that the indirect effect of the work environment to employee performance through organizational culture is the most dominant pathway compared with the direct and indirect pathways other. To improve employee performance needs to be improved work environment and strengthening organizational culture Dishubinfokom Sukoharjo.Keywords: Leadership, Work Environment, Compensation, Organizational Commitment, Organizational Culture, Employee PerformanceÂ